Prevalence and degree of bother of pelvic floor disorder symptoms among women from primary care and specialty clinics in Lebanon: an exploratory study. (January 2017) - Ghandour, Lilian; Minassian, Vatche; Al-Badr, Ahmed; Abou Ghaida, Rami; Geagea, Sandra; Bazi, Tony
Abstract Introduction and hypothesis The prevalence of pelvic floor disorders (PFD) and their impact on quality of life of women vary among different populations. The purpose of this study was to assess the prevalence of symptoms of PFD, and their degree of bother in a convenience sample of Lebanese women, and to evaluate health-care seeking (HCS) behavior related to PFD. Methods Women visiting clinics in a University Medical Center in Beirut, Lebanon, completed the self-filled validated Arabic version of the Global Pelvic Floor Bother Questionnaire (PFBQ). Data covering demographics, comorbidities, and HCS behavior related to PFD were collected. Total individual PFBQ scores, individual PFD symptom scores and HCS behavior were correlated to demographic data and comorbidities. Results The study participants included 900 women. PFBQ scores were significantly higher in women of older age, women with a lower level of education, women with higher vaginal parity, and women who engaged in heavy lifting/physical activity. BMI >25 kg/m2 was the strongest independent risk factor for the presence of PFD symptoms. The overall prevalence of urinary incontinence was 42 %. Anal incontinence was the most bothersome PFD. Almost two thirds of the women reported HCS due to any aspect of PFD. Among symptomatic women who believed that their PFD warranted HCS, financial concern was the most common obstacle irrespective of age and educational level. Conclusions In this convenience sample of Lebanese women, PFD symptoms were common and were significantly correlated with demographic characteristics and self-reported comorbidities. The key reason for not seeking health care related to PFD was financial concern.